2020
DOI: 10.3390/vaccines8020301
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Timeliness of Birth Dose Vaccination in Sub-Saharan Africa: A Systematic Review and Meta-Analysis

Abstract: Background: Depending on the epidemiological context of each country, three vaccines are recommended by the World Health Organization (WHO) to be administered as soon as possible after birth (birth vaccines); namely, BCG, zero dose of oral polio vaccine (OPV0), and birth dose of hepatitis B vaccine (HepB-BD). The timely administration of these vaccines immediately after birth might pose significant challenges in sub-Saharan Africa, where about half of childbirths occur outside health facilities. We therefore c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 50 publications
0
33
1
Order By: Relevance
“…By measuring the timeliness of HBV vaccination in Senegal, this study is one of the first to assess not only the coverage but also the effectiveness of a HBV vaccination programme in sub-Saharan Africa [ 27 ]. It is also the first study in Senegal, and one of the few in sub-Saharan Africa to date, to identify barriers to both BD timeliness and complete HBV vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By measuring the timeliness of HBV vaccination in Senegal, this study is one of the first to assess not only the coverage but also the effectiveness of a HBV vaccination programme in sub-Saharan Africa [ 27 ]. It is also the first study in Senegal, and one of the few in sub-Saharan Africa to date, to identify barriers to both BD timeliness and complete HBV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other countries in the region, the proportion of children with timely BD vaccination is high in Senegal. According to a recent systematic review, only 1.3% (95% CI, 0.0–4.5%) and 21.5% (95% CI, 9.4–36.8%) of children in sub-Saharan African countries that have introduced the BD received it within 24 h and seven days of birth, respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even after the introduction of HepB-BD into a country’s EPI, considerable challenges remain to reach a high level of coverage in the resource-limited African context. First, a recent meta-analysis of HepB-BD coverage in Sub-Saharan African countries where the dose is scheduled in the EPI reported that only 0.3% of babies born in healthcare facilities received the dose within 24 h of birth [ 11 ]. This highlights the importance of both providing clear guidelines for timely HepB-BD administration in healthcare facilities and ensuring the availability of the HepB-BD at all levels of the healthcare system [ 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These countries also face continued challenges to prioritize resource allocation for HepB-BD and advocate for action and investment in this vaccination strategy because of the lack of reliable information on the economic and financial costs required to integrate HepB-BD into their current EPI. Second, even in countries that have already introduced the HepB-BD into their EPI, coverage of timely HepB-BD administration remains low because of the logistical difficulties in administering the dose as scheduled (i.e., within 24 h of birth) to children born at home [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…696 This is because (a) only a few African countries have integrated HepB-BD in the national vaccination program; and (b) its timely administration is not sufficiently made even in countries that have integrated HepB-BD in their national program due to high rate of child birth at home. 97 Furthermore, HepB-BD is not perfect to prevent mother-to-child transmission from a high-risk mother. HBeAg-positive mothers exhibit a 20% risk of transmission to their offspring, despite neonatal immunoprophylaxis using HepB-BD.…”
Section: Prevention Of Hbv Mother-to-child Transmissionmentioning
confidence: 99%